2023
DOI: 10.3390/bios13010086
|View full text |Cite
|
Sign up to set email alerts
|

Multielectrode Arrays as a Means to Study Exocytosis in Human Platelets

Abstract: Platelets are probably the most accessible human cells to study exocytosis by amperometry. These cell fragments accumulate biological amines, serotonin in particular, using similar if not the same mechanisms as those employed by sympathetic, serotoninergic, and histaminergic neurons. Thus, platelets have been widely recognized as a model system to study certain neurological and psychiatric diseases. Platelets release serotonin by exocytosis, a process that entails the fusion of a secretory vesicle to the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In addition to brain imaging studies, SERTlight may also find use in other applications. A recent discovery indicated that platelets in a subset of Parkinson’s patients show reduced SERT expression levels. , Moreover, a link between platelets and depression has been postulated but remains poorly characterized . Platelets are recognized as 5HT storage units and models for studying 5HT uptake and release .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to brain imaging studies, SERTlight may also find use in other applications. A recent discovery indicated that platelets in a subset of Parkinson’s patients show reduced SERT expression levels. , Moreover, a link between platelets and depression has been postulated but remains poorly characterized . Platelets are recognized as 5HT storage units and models for studying 5HT uptake and release .…”
Section: Discussionmentioning
confidence: 99%
“…Human platelet isolation was conducted by modifying the Abcam ® method (Cambridge, UK) [16,17]. Briefly, nine milliliters of blood were taken by venipuncture from 10 participating volunteers.…”
Section: Human Platelets Preparationmentioning
confidence: 99%
“…Blood samples were subjected to serial centrifugation at room temperature with no brake [17]: (i) 200× g for 20 min; separating two-thirds of the supernatant or PRP (platelet-rich plasma); (ii) the PRP was mixed in a 1:1 ratio with a solution of HEPES buffer supplemented with prostaglandin E 1 (1 µM, final concentration). The mixture was centrifuged at 100× g for 15 min; (iii) the supernatant resulting from this second centrifugation was transferred to a sterile tube and centrifuged at 800× g for 20 min.…”
Section: Human Platelets Preparationmentioning
confidence: 99%
See 2 more Smart Citations